History as an element of persuasion in press coverage of the Israeli-Palestinian conflict (based on the example of "Polityka") - Marszał, Martyna (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume III, 2025)
This article analyzes how the weekly "Polityka" presented the Israeli-Palestinian conflict, focusing on the role of historical dates relevant to the course of the dispute. The study covered the years 2006 (Hamas's victory in the parliamentary elections) and 2023 (the escalation of the conflict). The aim of the analysis was to determine whether the references to specific historical dates were neutral or emotionally charged or biased, for example, by more often portraying one side of the conflict as the aggrieved party.